The millennial dynamics of malaria in the mediterranean basin: documenting Plasmodium spp. on the medieval island of Corsica - Boualam, Mahmoud Abdelwadoud; Corbara, Anne-Gaëlle; Aboudharam, Gérard; Istria, Daniel; Signoli, Michel; Costedoat, Caroline; Drancourt, Michel; Pradines, Bruno (Frontiers in Medicine, 2023)
The lack of well-preserved material upon which to base the paleomicrobiological detection of Plasmodium parasites has prevented extensive documentation of past outbreaks of malaria in Europe. By trapping intact erythrocytes at the time of death, dental pulp has been shown to be a suitable tissue for documenting ancient intraerythrocytic pathogens such as Plasmodium parasites.Methods: Total DNA and proteins extracted from 23 dental pulp specimens collected from individuals exhumed from the 9 th to 13 th century archaeological site in Mariana, Corsica, were analysed using open-mind paleo-auto-immunohistochemistry and direct metagenomics, Plasmodium-targeting immunochromatography assays. All experiments incorporated appropriate negative controls.Results: Paleo-auto-immunohistochemistry revealed the presence of parasites Plasmodium spp. in the dental pulp of nine teeth. A further immunochromatography assay identified the presence of at least one Plasmodium antigen in nine individuals. The nine teeth, for which the PfHRP-2 antigen specific of P. falciparum was detected, were also positive using paleoautoimmunohostochemistry and metagenomics.Dental pulp erythrocytes proved to be suitable for the direct paleomicrobiology documentation of malaria in nine individuals buried in medieval Corsica, in agreement with historical data. This provides additional information on the millennial dynamics of Plasmodium spp. in the Mediterranean basin.